Communication media to improve oral hygiene in children with hearing loss: Media komunikasi untuk meningkatkan oral hygiene pada anak dengan gangguan pendengaran - Mutiara, Asyifa; Fadel, Muhammad; Utami, Sri Pandu; Surya, Leny Sang; Zia, Hanim Khalida; Pertiwi, Oniel Syukma (Makassar Dental Journal PDGI Makassar, 2025)
Efforts to improve oral health can include efforts to increase knowledge, including promotive, preventive, curative, and rehabilita-tive efforts aimed at everyone. However, children with hearing loss require different media to educate them. This article examines the types of communication media in improving oral hygiene of children with hearing loss. The design used was a scoping re-view using Pubmed, Science Direct and Google Scholar databases using the keywords media, communication, oral hygiene, hearing loss and children and entering boolean AND and OR in the database search. The results of the research of all articles, the most widely used media is video (52%), followed by pictures (24%), sign language (12%) and the least is comics (6%) and dental models (6%). It is concluded that a variety of media can be used in improving OH of children with hearing loss, and re-quires children's attention and retention. The instructions delivered by the educator must be in accordance with the child's cog-nitive abilities.